GRAFFITI AS A FORM OF RHETORIC - Yelena Yerznkyan; Grisha Gasparyan (Armenian Folia Anglistika, 2021)
The article touches upon graffiti discourse as a form of rhetorical speech and tries to analyse it according to the three strategies of persuasion suggested by Aristotle: ethos, pathos and logos. The article reveals how specific the graffiti discourse is in terms of using these strategies and how the latter make the speech more powerful and persuasive. Also, an attempt is made to reveal the role of metaphor in the performance of the strategy of pathos in graffiti discourse.